2022
DOI: 10.1186/s12904-022-00904-9
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising effective symptom management in palliative care: a novel model derived from qualitative data

Abstract: Background Pain, breathlessness and fatigue are some of the most challenging symptoms to manage in patients with advanced disease. Specialist palliative care leads to better symptom management, but factors contributing to successful symptom management in this context have not been explored. Our aim was to understand what facilitates effective symptom management in specialist palliative care within UK hospices and investigate what barriers are experienced. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…A recent qualitative study by the authors confirm that patients at the end of life and their carers find it distressing to have to explain their situation repeatedly to primary care staff, including receptionists. 44 …”
Section: Discussionmentioning
confidence: 99%
“…A recent qualitative study by the authors confirm that patients at the end of life and their carers find it distressing to have to explain their situation repeatedly to primary care staff, including receptionists. 44 …”
Section: Discussionmentioning
confidence: 99%
“…36 A recent study found that the effectiveness of symptom management intervention is determined by family caregivers' roles and their understanding of task regarding symptoms management and interdisciplinary opinions. 37 The Least Offered Service in Palliative Home Care in Southeast and East Asia: Direct Care for Family…”
Section: The Most Common Services Offered In Palliative Homecarementioning
confidence: 99%
“…Healthcare professionals are competent to treat not just the underlying disease but also to provide holistic care to patients, individually and in the context of their families (Cheluvappa and Selvendran, 2022). In this holistic care, healthcare professionals can provide care for nausea or vomiting, pain management, and spiritual and psychological care for patients and their caregivers (Kozlov et al, 2018;Chapman et al, 2022;Coelho et al, 2022). By managing symptoms and providing spiritual and psychological care, healthcare professionals can provide comfort and minimize suffering for the person in palliative care and their family caregiver.…”
Section: Introductionmentioning
confidence: 99%